Phylogeography and population genetics of the Australian small carpenter bee, Ceratina australensis. (7th June 2018) - Oppenheimer, Robert L; Shell, Wyatt A; Rehan, Sandra M
Abstract: The Australian small carpenter bee, Ceratina australensis, is the sole member of the small carpenter bees, genus Ceratina, in Australia. Ceratina australensis is found throughout eastern Australia in dead, broken stems of weedy plant species, where it makes its nests. Here we developed eight microsatellite loci and used these markers to characterize the genetic structure of three populations across three distinct ecoregions that are connected by the Murray–Darling River basin. We genotyped 57 female bees and found significant and geographically consistent variation in allelic diversity and heterozygosity between populations. Through comparisons with the results of mitochondrial DNA screening from a previous study, we infer the possibilities of male-biased dispersal and limited interpopulation migration. Based on available distribution data, the expansion of C. australensis into arid regions appears to follow the Murray–Darling River basin and associated waterways. This basin has undergone severe anthropogenic disturbance since European settlement of Australia, with large-scale changes to native vegetation communities. Although it is unknown how these changes have affected local insect communities, C. australensis does not rely on a single plant species for nesting habitat. We provide evidence for the hypothesis that expansion of C. australensis into Australia might have been aided by the introduction of non-native pithy stemmed plants.